ANALISIS MODAL KERJA TERHADAP NPM (NET PROFIT MARGIN) PADA PT GUDANG GARAM TBK - Yanti; Aliah Pratiwi (JUIMA : JURNAL ILMU MANAJEMEN, 2020)
Working capital is not important for the company because without sufficient working capital, the company's operational activities cannot be carried out. The purpose of this study was to study working capital research on Net Profit Margins at PT Gudang Garam Tbk. This type of research is research that is associative. The data used is the financial statements of PT. Gudang Garam Tbk. year 2009 - 2018 which contains the allocation and income statement. The data was each obtained from the Indonesia Stock Exchange (IDX) and www.gudanggaramtbk.com. After processing the data, the results of the study show that working capital has no significant effect on changes in Net Profit Margin.